FACTORS OF IMPROVING STUDENTS' COMPETENCE IN THE LANGUAGE FIELD - Muminova Nargiza Abdurakhmanovna (The Conference Hub, 2025)
The article presents information on improving the competence of students. Also, theoretical information is provided and conclusions are drawn that competence is a necessary skill of every teacher.
Keywords: Education, knowledge, qualification, teacher, competence, competence.